2019
DOI: 10.1002/ecm.1391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil microbes on plant competition: a perspective from modern coexistence theory

Abstract: ETH Z€ urich, 8092 Z€ urich, Switzerland Citation: Ke, P.-J., and J. Wan. 2020. Effects of soil microbes on plant competition: a perspective from modern coexistence theory. Ecological Monographs 90(1):Abstract. Growing evidence shows that soil microbes affect plant coexistence in a variety of systems. However, since these systems vary in the impacts microbes have on plants and in the ways plants compete with each other, it is challenging to integrate results into a general predictive theory. To this end, we su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
118
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(119 citation statements)
references
References 84 publications
(224 reference statements)
1
118
0
Order By: Relevance
“…Meanwhile, we should also make sure that a proper design for a specific component effect should also help to eliminate or at least minimize the impacts from other confounding (or unwanted) effects. Since the methodologies for studying the effects of allelopathy (Inderjit & Callaway, 2003) and mediations from soil microbes (Hoeksema, 2015; Ke & Wan, 2020) have been well established, here we only focus on the other two, which are also the main interests in the current study.…”
Section: Further Thoughts On the Experimental Designs For Testing Thementioning
confidence: 99%
“…Meanwhile, we should also make sure that a proper design for a specific component effect should also help to eliminate or at least minimize the impacts from other confounding (or unwanted) effects. Since the methodologies for studying the effects of allelopathy (Inderjit & Callaway, 2003) and mediations from soil microbes (Hoeksema, 2015; Ke & Wan, 2020) have been well established, here we only focus on the other two, which are also the main interests in the current study.…”
Section: Further Thoughts On the Experimental Designs For Testing Thementioning
confidence: 99%
“…Theoretical and empirical studies have shown that plant-soil feedbacks can influence whether a pair of species coexist if they drive stabilizing feedback loops that favor species that fall to low abundance and disadvantage more abundant species (or destabilizing loops that favor more abundant species and disadvantage rare ones) (Bever et al 1997, Crawford et al 2019). However, recent theoretical advances have clarified that species coexistence is also determined by the degree to which soil micobes mediate an average fitness difference that gives one species a demographic advantage over its competitor, regardless of its abundance in the system (Chesson 2000, Kandlikar et al 2019, Ke and Wan 2019). Here, we show that empirically quantifying the microbially mediated fitness difference and comparing it to the degree of microbial stabilization in Bever et al (1997)’s classic model of plant-soil feedback is essential for understanding how soil microbes shape plant species coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors produce both effects (Song et al, 2019). In particular, Janzen-Connell effects produce a stabilizing mechanism; however, they can also produce competitive differences if species are differently susceptible to their natural enemies (Stump & Comita, 2018;Ke & Wan, 2019;Kandlikar et al, 2019), or if enemy spillover is occurring (Stump, 2017). Thus, a more modern view of the Janzen-Connell hypothesis is that Janzen-Connell effects are a factor producing stabilizing mechanisms-likely one of manyand that they can allow coexistence if they are stronger than any competitive differences in the community.…”
Section: Coexistence Theorymentioning
confidence: 99%
“…4). Differential susceptibility also produces competitive differences (Stump & Comita, 2018;Ke & Wan, 2019;Kandlikar et al, 2019): if a species is highly susceptible to its natural enemies, and most seeds of that species are unable to disperse away from those enemies, then that species will be at a disadvantage compared to species that can tolerate their natural enemies (Stump & Comita, 2018) (Fig. 4).…”
Section: Strength Of Susceptibilitymentioning
confidence: 99%